2002
DOI: 10.1152/ajpendo.00101.2001
|View full text |Cite
|
Sign up to set email alerts
|

Progressive increase in human skeletal muscle AMPKα2 activity and ACC phosphorylation during exercise

Abstract: . Progressive increase in human skeletal muscle AMPK␣2 activity and ACC phosphorylation during exercise. Am J Physiol Endocrinol Metab 282: E688-E694, 2002; 10.1152/ajpendo.00101.2001.-The effect of prolonged moderate-intensity exercise on human skeletal muscle AMP-activated protein kinase (AMPK)␣1 and -␣2 activity and acetyl-CoA carboxylase (ACC␤) and neuronal nitric oxide synthase (nNOS) phosphorylation was investigated. Seven active healthy individuals cycled for 30 min at a workload requiring 62.8 Ϯ 1.3% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
130
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 35 publications
(68 reference statements)
10
130
2
3
Order By: Relevance
“…Two of the studies reported no change in malonyl-CoA concentration (36,37), whereas a more recent study has reported a significant decrease in malonyl-CoA and ACC activity following exercise (38). The latter study appears to be consistent with studies reporting an increase in human muscle AMPK activity with exercise (39,40) and supports the notion that a decrease in malonyl-CoA during exercise allows for an increase in the rate of LCFA oxidation.…”
Section: Discussionsupporting
confidence: 71%
“…Two of the studies reported no change in malonyl-CoA concentration (36,37), whereas a more recent study has reported a significant decrease in malonyl-CoA and ACC activity following exercise (38). The latter study appears to be consistent with studies reporting an increase in human muscle AMPK activity with exercise (39,40) and supports the notion that a decrease in malonyl-CoA during exercise allows for an increase in the rate of LCFA oxidation.…”
Section: Discussionsupporting
confidence: 71%
“…It has been postulated that NO and AMPK are part of the same signalling pathway. During exercise, AMPK phosphorylates nNOSμ in human skeletal muscle [46][47][48], while in rat skeletal muscle glucose uptake stimulated by the AMP analogue, 5-aminoimidazole-4-carboxamide ribonucleoside, which activates AMPK, can be blocked by an NOS inhibitor [49]. Further studies are required to clarify the relationship between NO and AMPK with regard to glucose uptake.…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…Physical exercise has recently emerged as a potential treatment for sarcopenia (Montero-Fernandez and Serra-Rexach 2013;Crane et al 2013), associated with benefits in musculoskeletal systems (Manabe et al 2013) and metabolic function (Stephens et al 2002). In mice, spontaneous wheel running may provide an excellent model to counteract the deterioration of motor skills and skeletal function associated with aging due to the fact that it is a voluntary rhythmic behavior, generally performed with a high degree of consistency and coordination.…”
mentioning
confidence: 99%